Clinical and Radiographic Outcomes of the Ream-and-Run Procedure for Primary Glenohumeral Arthritis. (2nd August 2017) - Somerson, Jeremy S.; Neradilek, Moni B.; Service, Benjamin C.; Hsu, Jason E.; Russ, Stacy M.; Matsen, Frederick A.
Abstract : Background: The ream-and-run procedure can provide improvement in shoulder function and comfort for selected patients with primary glenohumeral arthritis who wish to avoid a prosthetic glenoid component. The purpose of this study was to evaluate factors associated with medialization of the humeral head after this procedure as well as the relationship of medialization to the clinical outcome. Methods: We collected patient, shoulder, and procedure characteristics along with Simple Shoulder Test (SST) scores before surgery and at the time of follow-up. Medialization was determined by comparing the position of the humeral head prosthesis in relation to the scapula on postoperative baseline radiographs made within 6 weeks after surgery with that on comparable follow-up radiographs made ≥18 months after surgery. Results: Two-year clinical outcomes were available for 101 patients (95% were male). Comparable radiographs at postoperative baseline and follow-up evaluations were available for 50 shoulders. For all patients, the mean SST score (and standard deviation) increased from 4.9 ± 2.8 preoperatively to 10.3 ± 2.4 at the latest follow-up (p < 0.001). Significant clinical improvement was observed for glenoid types A2 and B2. Shoulders with a type-A2 glenoid morphology, with larger preoperative scapular body-glenoid angles, and with lower preoperative SST scores, were associated with the greatest clinical improvement. Clinical outcome was not significantly associated with the amount of medialization. Conclusions: The ream-and-run procedure can be an effective treatment for advanced primary glenohumeral osteoarthritis in active patients. Further study will be necessary to determine whether medialization affects the clinical outcome with follow-up of >2 years. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.